2021
DOI: 10.1093/cid/ciab428
|View full text |Cite
|
Sign up to set email alerts
|

Tracing People Living With Human Immunodeficiency Virus Who Are Lost to Follow-up at Antiretroviral Therapy Programs in Southern Africa: A Sampling-Based Cohort Study in 6 Countries

Abstract: Background Attrition threatens the success of antiretroviral therapy (ART). In this cohort study, we examined outcomes of people living with HIV (PLHIV) lost to follow-up (LTFU) 2014-2017 at ART programs in Southern Africa. Methods We confirmed LTFU (missed appointment for ≥60 or ≥90 days, according to local guidelines) by checking medical records and used a standardized protocol to trace a weighted random sample of PLHIV who… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 33 publications
2
23
0
Order By: Relevance
“…Mortality rates in 2017 were an average 60% and 73% lower than in 2005, in and outside of Africa, respectively, after controlling for individual characteristics, and with some variation by age, region and ART duration. However, our adjusted analysis, using novel IeDEA tracing study data [11,12], suggests that analyses using only routine programme data may substantially underestimate mortality. The aggregate observed in mortality estimates in our and other studies [24] suggest that guideline and programme implementation changes have improved child outcomes.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Mortality rates in 2017 were an average 60% and 73% lower than in 2005, in and outside of Africa, respectively, after controlling for individual characteristics, and with some variation by age, region and ART duration. However, our adjusted analysis, using novel IeDEA tracing study data [11,12], suggests that analyses using only routine programme data may substantially underestimate mortality. The aggregate observed in mortality estimates in our and other studies [24] suggest that guideline and programme implementation changes have improved child outcomes.…”
Section: Discussionmentioning
confidence: 89%
“…We also utilized data from a recent IeDEA tracing study in six treatment programmes in five countries (Zambia, Malawi, Zimbabwe, Lesotho and Mozambique) in southern Africa. From the traced sample of 3256 persons classified as LTFU by participating programmes [11,12], we used the subsample of CHIV aged younger than 15 years, who had not visited the clinic for at least the previous 120 to 180 days, depending on local definitions of LTFU. The children's outcomes were determined using phone calls and home visits.…”
Section: E T H O D S 21 Data Sourcesmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 In recent years, up to 40% of those LTFU in the African region were found to have died. 3,4 Studies from the Australian HIV observational database found the LTFU rate to be 3.9/100PYS. Linkages with the Australian National Death Index revealed a subsequent mortality rate of 8.6% among those LTFU.…”
Section: Introductionmentioning
confidence: 99%